Assessment of reticulocyte-haemoglobin equivalent (Ret-He) as a diagnostic indicator for iron deficiency anaemia - Bakri, Noor Amalia; Mohd Tohit, Eusni Rahayu; Idris, Faridah; Ismail, Rusmawati (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Iron deficiency anaemia (IDA) is the most common cause of anaemia. The diagnosis of IDA, however, remains a challenge and is a problem worldwide. Serum iron study is commonly used for IDA diagnosis but there are some limitations. This study was conducted to evaluate reticulocyte-haemoglobin equivalent (Ret-He) as a screening tool for IDA diagnosis in adults. Method: This is a comparative case control study conducted in Hospital Tengku Ampuan Afzan, Kuantan consisting of adult patients with iron deficiency anaemia and a healthy control group. Haematological parameters (Hb, RBC count, MCV, MCH, RDW) inclusive of Ret-He and serum iron parameters (serum iron, transferrin saturation and serum ferritin) were measured. Correlation between Ret-He with other haematological and serum iron parameters were analysed. Results: There were 103 IDA adult patients with majority of them being female (85.4%) with median age of 36 years old. Malay ethnicity (79.6%) contributed to the larger proportion of adult IDA patients. The Ret-He value for patient and control groups were 16.50 ± 4.90 pg and 34.80 ± 1.97 pg, respectively. Ret-He was 89.32% sensitive and 100% specific with 100% positive predictive value (PPV) and 73.11% negative predictive value (NPV) when compared to transferrin saturation. There was significant correlation between Hb, MCH, MCV, RDW and serum iron, transferrin saturation and serum ferritin parameters with Ret-He. Conclusion: Ret-He together with a complete blood count, may serve as an alternative to the serum iron parameters for screening of IDA in adults.